Neuroglia Molecular Mechanisms in Psychiatric Disorders - Caterina Scuderi; Mami Noda; Alexei Verkhratsky (Frontiers Media SA, 2019)
Neuropsychiatric disorders have long been considered as specific dysfunctions of neuronal functions. Studies of the recent decade, however, have challenged this simplistic view, highlighting the important role played by neuroglial cells in the onset and/or progression of neuropsychiatric diseases. In the central nervous system (CNS) non-excitable neuroglia are represented by cells of ectodermal origin (astrocytes, mainly responsible for CNS homeostasis and oligodendrocytes that provide myelination and support for axons) and mesodermal origin (microglial cells that are scions of foetal macrophages entering the neural tube early in development; these cells provide for CNS defence and contribute to shaping neuronal networks). Pathological changes of neuroglia are complex; these changes are classified into reactive gliosis (astrogliosis, activation of microglia and hypertrophy of oligodendroglial precursors), gliodegeneration with loss of function and glial pathological remodelling. Combination of these processes defines the evolution of neurological diseases in general and neuropsychiatric disorders in particular. In this research topic we addressed the contribution of neuroglia to major neuropsychiatric pathologies including major depression, schizophrenia, and addictive disorders.
English
Keywords: Neuropsychiatric Disorders; Alcohol Use Disorders; Neurovascular Disorders; Neuroglia; Schizophrenia; Major Depression